2007
DOI: 10.1097/qad.0b013e3282ed6338
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancers during interrupted antiretroviral therapy in the SMART study

Abstract: Non-AIDS-defining malignancies were more common in this cohort than AIDS-defining malignancies. This analysis provides further evidence against the use of CD4 T-cell-guided ART because of a higher risk of AIDS-defining malignancies in addition to opportunistic infections and deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 35 publications
7
78
0
4
Order By: Relevance
“…In our study, the absence of any antiretroviral treatment for 3 months or more was associated with an eight-fold increased KS risk, thus confirming the danger of treatment interruption already reported with respect to progression to AIDS or death (Holkmann et al, 2007). Significantly higher KS incidence among PWHA who were assigned to the CD4 cell-guided intermittent antiretroviral treatment arm than those assigned to the continuous treatment arm was also shown in a randomised clinical trial (Silverberg et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…In our study, the absence of any antiretroviral treatment for 3 months or more was associated with an eight-fold increased KS risk, thus confirming the danger of treatment interruption already reported with respect to progression to AIDS or death (Holkmann et al, 2007). Significantly higher KS incidence among PWHA who were assigned to the CD4 cell-guided intermittent antiretroviral treatment arm than those assigned to the continuous treatment arm was also shown in a randomised clinical trial (Silverberg et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…Although this study is not based on a strategic trial, and cannot establish that increasing the CD4 counts after starting cART caused the decrease in non-AIDS-defining malignancies, it does suggest that earlier treatment may be beneficial for reducing the incidence of non-AIDS-defining malignancies. This is supported also by recent data from the Strategies for Management of Antiretroviral Therapy study, where patients in the drug conservation arm who interrupted treatment had a higher rate of AIDS-defining malignancies, 47 which was thought to be because of lower CD4 cell counts and higher viral loads. The Strategic Timing of Antiretroviral Therapy trial to determine whether starting cART early (before CD4 drops to <500 cells/mm 3 ), rather than waiting until CD4 drops to <350 cells/mm 3 as current guidelines recommend, reduces the occurrence of serious morbidity and mortality, will also explore whether cART protects against non-AIDS-defining malignancies.…”
Section: Discussionmentioning
confidence: 58%
“…The most common malignancies were anal cancer, basal cell carcinoma, Hodgkin’s lymphoma, and lung cancer. Although other HIV-infected cohort studies have reported similar observations [4,8,23] and suggest that the incidence of NADC is on the rise in the potent ART era [4,8], the longitudinal and robust nature of the ACTG database provided a unique opportunity to examine predisposing factors for cancer. Indeed inclusion of ART-naïve patients starting ART provided important information on factors associated with an increased risk of NADCs among HIV-infected patients.…”
Section: Discussionmentioning
confidence: 90%